REMARKS ON INTENSIFIERS AND INTENSIFICATION IN ENGLISH AND ROMANIAN - Constantin MANEA (Studii de gramatică contrastivă, 2014)
The aim of the present paper is to briefly illustrate and assess the main uses of intensifiers and intensification in English and Romanian, trying to hint at the complexity of the phenomenon in the two languages, while sketchily suggesting ways to improve the teaching and learning activities in Romanian schools, as well as much of the activity of translators in this country. The authors’s illustrative treatment tackles the broader sphere of intensification, not only such intensifiers as very, terribly, awfully, really, definitely, kind of. The main subsections of the paper deal, respectively, with semantic aspects, word formation, syntactic aspects, stylistic issues, and a few remarks on usage.